Comparison Of Four Anti-Avian IgY Secondary Antibodies Used In Western Blot And Dot-Blot ELISA To Detect Avian Bornavirus Antibodies In Four Different Bird Species - Escandon P (Dove Medical Press, 2019)
Paulina Escandon,1,2 J Jill Heatley,1,3 Luc R Berghman,2,4 Ian Tizard,1,2 Jeffrey MB Musser1,2 1Schubot Exotic Bird Health Center, College of Veterinary Medicine, Texas A&M University, College Station, TX 77843, USA; 2Department of Veterinary Pathobiology, College of Veterinary Medicine, Texas A&M University, College Station, TX 77843, USA; 3Department of Small Animal Clinical Sciences, College of Veterinary Medicine, Texas A&M University, College Station, TX 77843, USA; 4Department of Poultry Science, College of Agriculture & Life Sciences, Texas A&M University, College Station, TX 77843, USACorrespondence: Jeffrey MB Musser4467 TAMU, VTPB, College of Veterinary Medicine, College Station, TX 77843-4467, USATel +1 979 458 9946Fax +1 979 458 0321Email Jmusser@cvm.tamu.eduPurpose: This study evaluated the specificity of different avian secondary antibodies used in Western blot and dot-blot ELISA to detect avian bornavirus antibodies in bird plasma.Methods: Plasma samples were collected from: two Blue and gold macaws, one positive and one negative for avian bornavirus by RT-PCR; a Cockatiel and a Monk parakeet prior to and following experimental infection; and, two Mallards, one positive and one negative for avian bornavirus by RT-PCR Samples were analyzed by Western blot and dot-blot ELISA that incorporated recombinant avian bornavirus nucleoprotein as the target analyte. Four species-specific anti-IgY secondary antibodies were used in the assays: goat anti-macaw IgY, goat anti-bird IgY, goat anti-duck IgY, and rabbit anti-chicken IgY.Results: In the Western blot, anti-macaw IgY secondary antibody produced strong signals with Blue and gold macaw and Cockatiel positive plasma, but no signal with Mallard positive plasma. Anti-bird IgY secondary antibody produced strong signals with Blue and gold macaw, Cockatiel, and Mallard positive plasma. Anti-duck and anti-chicken IgY secondary antibody produced a strong and moderate signal, respectively, only with Mallard positive plasma. In the dot-blot ELISA, there was a distinct and significant difference (P<0.05) in the signal intensity between the different secondary antibodies within a bird species. Anti-macaw IgY secondary antibody produced significantly (P<0.05) stronger signals than the other secondary antibodies in Blue and gold macaw, Cockatiel, and Monk parakeet positive plasma, while anti-duck IgY secondary antibody produced significantly (P<0.05) stronger signals than the other secondary antibodies in Mallard positive plasma.Conclusion: In testing psittacines with immunoassays, and especially in assays that incorporate short incubation reaction times such as a dot-blot ELISA, species-specific anti-IgY secondary antibodies provided more accurate results.Keywords: immunodiagnostics, serology, proventricular dilatation disease, avian ganglioneuritis